Regulating flow of vapor to enhance pool boiling. (25th February 2019) - Hayes, Austin; Raghupathi, Pruthvik A.; Emery, Travis S.; Kandlikar, Satish G.
Highlights: 3-D printed features are developed to enhance the boiling performance. The features are hollow conical structures that structure the liquid and vapor flow. Miniaturized hollow conical structures further improve the boiling performance. The structures can be combined with other enhancement techniques like microchannels. Abstract: High heat flux dissipation can be achieved in pool boiling by regulating vapor removal to induce a streamlined motion of liquid over the heater surface. In the present work, a novel approach is presented by directing the vapor through specific structures to generate separate liquid-vapor pathways. A hollow conical structure (HCS) is printed above the heater surface using metal additive manufacturing to induce this effect. As the liquid boils and vapor accumulates inside the HCS, independent liquid and vapor flow fields are formed at the top and side holes of the HCS. The direction of liquid and vapor flow is determined by the size of the top hole in the HCS. If the top hole is larger than the departure bubble diameter, vapor naturally escapes from the top and liquid enters through the side holes. A smaller top hole induces a reversal of this motion and causes the vapor to exit through the side holes and liquid to enter from the top hole. To isolate the convective effects on boiling enhancement from the fin effect, the HCS was thermally insulated from the heater surface. The results indicated that 74% of the boiling enhancement achieved with these structures resulted from the convective heat transfer in the developing flow region. The boiling performance was further increased using multiple HCS of a smaller footprint over microchannels to improve heat transfer in the entrance region. This resulted in a 2-fold increase in CHF and a 4-fold increase in HTC compared to plain surface.